The red gum condition index: a multi-variable tree condition index for visually assessed river red gum (Eucalyptus camaldulensis) trees. Issue 1 (2nd January 2019) - Souter, Nicholas J.
ABSTRACT: River red gum ( Eucalyptus camaldulensis ) is the dominant floodplain tree of the River Murray in south-eastern Australia. Drought and over-allocation of water have seen tree condition decline and environmental water is being used to aid recovery. An eight-variable visual assessment method is widely used to assess river red gum condition. These variables have been combined into a single aggregated index, the Red gum Condition Index (RCI), which comprises the Crown Condition sub-index (CCsi), which contributes 60% of the final score and assesses the amount of foliage in the tree crown; and the Secondary Variable sub-index (SVsi) which contributes 40% of the final score and aggregates measures of new tip growth, epicormic growth, reproduction, leaf die-off, mistletoe and bark condition. Relationships between variables define six condition categories. The R software package RCI calculates the RCI and provides quantitative and graphical outputs. Applied to two sites in South Australia, the RCI detected changes in tree condition attributable to environmental watering. As a responsive index with transparent categories the RCI can measure the current condition of river red gum stands and assess their watering needs. The RCI approach is readily transferrable to other tree species.